Do loyalty customers feel manipulated by preservice suggestive tipping? A moderated mediation model - Lenglain, Matthieu Jean (My University, 2025)
Pre-service tipping is a new and growing trend of tipping in which consumers pay tips upon order placement, specifically before the fulfillment of service (Warren et al., 2021). Fan et al. (2024) investigated that the implementation of suggestive tipping can nudge consumers to tip. Research in tipping behavior has primarily focused on post-service tipping: There is a need to focus on how suggestive tipping formats influence consumers’ tipping behavior in the preservice tipping phase. Warren et al. (2021) found whether preservice tipping led consumers to question whether the service provider had manipulative intentions. Furthermore, preservice tipping creates high levels of uncertainty (Wen et al., 2024), where consumers have not yet been served. When loyalty is high, consumers tend to trust the information provided by the restaurant (Chang et al., 2013). The purpose of this study is to investigate suggestive tipping format and consumers’ loyalty interactively influence their perceived manipulation. This study also examines consumers’ perception of how manipulation mediates the interactive effect of the tipping format, loyalty, and willingness to tip. The objective of this study is to examine the moderated effect of customers’ loyalty (LOY) on the mediating effect of perceived manipulativeness (PM) on the relationship between suggestive tipping (ST) and willingness to tip (WTT). Drawing on the elaboration likelihood model (ELM), the results suggest that when consumers’ loyalty is low, all three formats, which are the following: F#1 is that consumers are presented with only customary percentages for a given amount of the check (15%, 18%, and 20%). The second format (F#2) presents not only the customary percentage but also the tip dollar amounts based on the tip percentage: 15% ($2.25), 18% ($2.70), and 20% ($3.00). In the last format (F#3), consumers are presented with customary percentages along with the total amount of the bill after tip—15% ($17.25), 18% ($17.70), and 20% ($18.00)—of suggestive tipping is perceived as manipulative by consumers, leading to lower willingness to tip. However, when consumers’ loyalty is high, the tipping suggestion format with both percentage and tip dollar amount was perceived as less manipulative, which results in a higher willingness to pay. The results suggest that loyal consumers would still prefer the calculation assistance format with percentage and dollar amount in the preservice context. We argue that when the information displayed is written and clearly expressed, consumers feel less manipulated and are more likely to tip more. The findings of this study carry several important implications for restaurant management and customer behavior. First, preservice tipping is perceived as inherently risky, even among loyal consumers. Restaurant managers may apply these insights by strategically designing tipping suggestions that display both percentage and tip dollar amounts, which could enhance consumer motivation to tip more generously. Second, the study highlights the importance of consumer loyalty, as loyal consumers tend to feel less manipulated when presented with suggestive tipping amounts. Restaurant practitioners should prioritize strengthening their loyalty programs, aiming to encourage repeat patronage where consumers are more receptive to preservice tipping suggestions.
Keywords: Tipping; Preservice tipping; Loyalty; Perceived manipulativeness; Willingness to tip